A multi-level model integrating corporate social responsibility and political activity in the European Union: What are the institutional implications for foreign companies? - Borges, A.; Ramalho, N. (Corporate Social Responsibility and Environmental Management, 2024)
Many multinational corporations develop business operations in Europe. The current research attempts to fill the gap on how corporations can increase their political influence in this geography by exploring the joint effect of corporate political activity (CPA) and social responsibility (CSR) on political embeddedness and financial performance. Based on institutional theory and on a sample of autochthonous (European Union [EU]) and allochthonous (non-EU) firms with declared EU lobbying (from 2008 to 2019) we conducted two studies. Based on a multi-level model, Study 1 finds strong and robust evidence that boardroom gender diversity and EU lobbyists interactively increase EU political embeddedness. Complementarily, Study 2, which relies on general linear Modeling, suggests that allochthonous corporations are more profitable when they display high-level political embeddedness and lobbying expenditures, combined with adoption of United Nations (UN) guidelines. Overall, findings show that lobbying in Europe pays off, especially when corporations strive to be aligned with EU ethical values and aspirations. Hiring lobbyists to be based in Brussels and promoting gender equality help establish EU political connections. Subsequently, findings highlight the role that EU political embeddedness, lobbying expenditures, and UN guidelines play in leveraging financial performance, especially across non-EU corporations. Regarding EU corporations, results show that a firm-level investment on CPA-CSR is particularly important. Overall, findings from this research support corporations that are growing businesses in Europe.